Probing electronic correlations in actinide materials using multipolar transitions - Bradley, J. A.; Haverkort, Maurits W. (Arxiv, 2010)
We report nonresonant inelastic x-ray scattering from the semi-core 5d levels of several actinide compounds. Dipole-forbidden, high-multipole features form a rich bound-state spectrum dependent on valence electron configuration and spin-orbit and Coulomb interactions. Cross-material comparisons, together with the anomalously high Coulomb screening required for agreement between atomic multiplet theory and experiment, demonstrate sensitivity to the neighboring electronic environment, such as is needed to address long-standing questions of electronic localization and bonding in 5f compounds.